The Writing Problem: Teacher Self-Efficacy and Instruction (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Writing is a struggle for many secondary students. The Common Core State Standards and state testing cause an increased focus on writing, but there has been little improvement in performance. The writing problem is no longer an English Language Arts (ELA) problem. All content areas need to work to improve student writing ability. This article explores two causes of low student writing ability: low teacher self-efficacy and ineffective teacher education programs. In order for students to become better writers, teachers not only need to become better writers, but also believe that they are better writers. And teacher education programs need to support teacher candidates with writing instruction specifically tailored to their content area so they are prepared to teach students how to write.